Barracks as the Main Type of Mass Housing in the Soviet Industrial Towns Constructed During the First Five-Year Plans - Meerovich, Mark; Bulgakova, Elena (project baikal, 2019)
In the period of Soviet industrialization (1920-1940s), Sotsgorod new developments were often erected from scratch – in steppe, taiga or the desert. Their workforce recruitment was impossible without large-scale housing. Barracks were the first truly mass housing to be built in Sozgorod new developments in the industrialization period. They were a mass phenomenon providing a roof for about 80-90% of the population of industrial settlements.
Keywords: barracks; Sotsgorod; industrialization; Soviet policy of urbanization